Representasi Perpustakaan dalam Film Nasional (Analisis Semiotika Roland Barthes) - Ibrahim, Andi; K, Ratna; Tahir, Arsil (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2023)
This research focuses on the representation of libraries in national films. The primary objective of this study is to analyze how libraries are portrayed in films using a semiotic analysis approach, primarily drawing from Roland Barthes' theory. The research methodology employed is qualitative descriptive with a semiotic analysis approach based on Roland Barthes' theory. The findings of this research reveal various representations of libraries in several national films featuring library scenes and librarians. Some of the national films examined include